A New Index for Obstetric Safety and Quality of Care: Integrating Cesarean Delivery Rates With Maternal and Neonatal Outcomes. Issue 1 (22nd March 2023) - Ramani, S.; Halpern, T.A.; Akerman, M.; Ananth, C.V.; Vintzileos, A.M.
Abstract : ( Am J Obstet Gynecol . 2022;226:556.e1–9) Cesarean delivery rates have been used as an outcome quality measure for evaluating obstetricians and hospitals. This rate, however, does not account for high-risk maternal factors. This study aimed to create and evaluate a new metric for comparing the quality of obstetric care, using the cesarean delivery rate among nulliparous patients with vertex-presenting singleton fetuses at term adjusted for pre-delivery maternal risk factors, neonatal morbidities, and maternal morbidities.